Key techniques in cognitive behavioral therapy for insomnia in adults and recommendations for workflow improvements - ZHANG Peng; CHEN Tao; XU Li (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Cognitive behavioral therapy for insomnia (CBT ⁃ I) boasts convincing evidence from randomized controlled clinical trials, yet its practical application encounters substantial barriers. This paper analyzes the key techniques and challenges of CBT ⁃I, proposing the following workflow improvements to enhance its clinical application and benefit more insomnia patients.